Effectiveness and safety of standard chemotherapy in older patients with ovarian cancer: a retrospective analysis by age group and treatment regimen - Brezis, Miriam R.; Shachar, Eliya; Peleg Hasson, Shira; Laskov, Ido; Michaan, Nadav; Levy, Bar; Wolf, Ido; Safra, Tamar (Frontiers in Oncology, 2023)
Objective: To evaluate the effectiveness and safety of standard chemotherapy administered to patients >70 years with advanced ovarian cancer (OC).: Medical records of 956 advanced-stage patients with OC treated between 2002-2020 with standard surgery and paclitaxel-carboplatin chemotherapy in a threeweekly (PC-3W) or weekly (PC-1W) regimen were reviewed. Treatment response and tolerability were compared between patients ≤70 years (N=723) and >70 years (N=233) with stratification to septuagenarians (>70-80 years) and octogenarians (>80 years).Results: Median overall survival (mOS) in patients >70 was 41.26 months (95% confidence interval [Cl], 37.22-45.14) and median progression-free survival (mPFS) was 11.04 months (95% Cl, 8.97-15.74). No statistically significant differences in mPFS and mOS were observed between septuagenarians and octogenarians. Patients >70 treated with PC-1W vs PC-3W had significantly longer mOS (57.17 vs 30.00 months) and mPFS (19.09 vs 8.15 months). Toxicity rates were mostly similar between younger and older patients. Among patients >70 treated with PC-1W, the rate of neutropenia (75.7% vs. 51.8%, p=0.0005), thrombocytopenia (41.0% vs.22.2%, p=0.0042) and anemia (78.1% vs. 51.9%, p<0.0001) were significantly higher and the rate of grade 2 alopecia was statistically significantly lower compared with those >70 treated with PC-3W. Significantly more patients treated with PC-1W completed ≥6 chemotherapy cycles, suggesting better tolerability of this regimen.Older patients with OC may benefit from improved OS with reasonable toxicity if treated with standard chemotherapy. Older patients treated with PC-1W are more likely to complete the full chemotherapy course and survive longer compared with those treated with conventional PC-3W.